(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
The research interest has focused on various herbs that possess antidepressant properties and may be useful adjuncts in helping the management of depression in humans. The present study was therefore designed to investigate the antidepressant-like effects of methanol leaf extract of Ichnocarpus frutescens in animal models of depression. The mice were divided in to different groups and treated with two different doses of methanol extracts (200 & 400 mg/kg), same doses of extracts with different antagonist of 5HT, NA & DA (Ondansetran, Terazosin & Chlorpromazine) and standard groups treated with imipramine 10mg/kg. All groups of animals were separately submitted to forced swim test (FST), and Tail suspension test (TST) tests for the bio-screening of leaf extract with antidepressant profile. Results revealed that the immobility time in the FST & TST was significantly reduced with extracts alone and extracts with Chlorpromazine treated group compared to negative control. There is no significant reduction in immobility time was observed particularly in rats orally administered extracts with Ondansetran & Terazosin when compared with their respective controls. Thus, it is suggested that methanol leaf extract of Ichnocarpus frutescens exhibited significant antidepressant-like effects in animal models of depression and may be served as a potential resource for natural psychotherapeutic agent, against depression and its may act mostly through modifying serotonergic and noradrenergic neurons.